1985
DOI: 10.1002/1097-0142(19850215)55:4<691::aid-cncr2820550403>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for stage IV Hodgkin's disease treated with MOPP, with or without bleomycin

Abstract: Prognostic factors for 53 previously untreated patients with Stage IV Hodgkin's disease were analyzed for their effects upon complete remission rate, survival, and disease‐free survival following treatment with mechlorethamine, Oncovin (vincristine), procarbazine, and prednisone (MOPP) or MOPP plus bleomycin (MOPP‐Bleo). Although 75% of those patients with only one site of extranodal disease achieved complete remission, only 25% of those with more than one site of involvement entered complete remission. Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…The superior outcome with ABVD consolidation may be primarily for patients with pathology other than nodular sclerosis [5,6]. The overall 71% CR rate for patients in this study, 22% of whom had involvement at more than one extranodal site is compatible with the results of Pillai et al [7] in a similar group of patients treated with similar induction therapy, and with those of Sullivan et al [8] obtained in children with involved field RT followed by MOPP-Bleo. It is also similar to the CR rate with MOPP alternating with ABVD as induction therapy reported by Canellos et al [9].…”
Section: Discussionsupporting
confidence: 87%
“…The superior outcome with ABVD consolidation may be primarily for patients with pathology other than nodular sclerosis [5,6]. The overall 71% CR rate for patients in this study, 22% of whom had involvement at more than one extranodal site is compatible with the results of Pillai et al [7] in a similar group of patients treated with similar induction therapy, and with those of Sullivan et al [8] obtained in children with involved field RT followed by MOPP-Bleo. It is also similar to the CR rate with MOPP alternating with ABVD as induction therapy reported by Canellos et al [9].…”
Section: Discussionsupporting
confidence: 87%
“…This would allow effective but less morbid treatments to be given to low risk patients and more intensive therapy to be reserved for patients at higher risk. A number of factors which predict lower CR rates have been described and these include advanced stage (Longo et al, 1986), presence of systemic (B) symptoms (Longo et al, 1986), number of extranodal sites (Pillai et al, 1985), and drug dose intensity (Longo et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Factors which predict the length of CR include B symptoms (Cosset et al, 1984;Tubiana et al, 1985;Longo et al, 1986), stage (Haybittle et al, 1985;Sutcliffe et al, 1984;Horwich et al, 1986), histology (Haybittle et al, 1985;Sutcliffe et al, 1984;Specht et al, 1987), number of disease sites (Cosset et al, 1984;Tubiana et al, 1985;Horwich et al, 1986), age (Sutcliffe et al, 1984;Tubiana et al, 1985;Longo et al, 1986), male sex (Tubiana et al, 1985;Specht et al, 1987), erythrocyte sedimentation rate (ESR) (Haybittle et al, 1985;Tubiana et al, 1985), tumour burden (Specht et al, 1987), number of extranodal sites (Longo et al, 1986), the presence of bulky mediastinal disease (Hoppe et al, 1982), time to achieve CR (Longo et al, 1986) and drug dose intensity (Pillai et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…n = 104 analysis included response as a factor. The two centres (DeVita et al, 1980;Carde et al, 1983) who examined pleural involvement found it significant, as did the two centres (Peterson, 1982;Pillai et al, 1985) examining the number of sites of extra-nodal disease. Only DeVita et al (1980) found histological subtype to be important, patients E. = 47 with nodular sclerosing pathology having a significantly shorter survival than the rest.…”
Section: Methodsmentioning
confidence: 99%